0
$\begingroup$

Related to my most recent post, I have a question I get stuck in.

Let $\phi$ and $\Phi$ be the standard normal density and distribution function, respectively. Show that $f(x)=2\phi(x)\Phi(\lambda x)$ is a probability density function for some random variable ($\lambda,x \in \mathbb{R}$). Hint. Use $\Phi(\lambda x)=1-\Phi (- \lambda x)$ and argue on symmetry.

My attempt was to show that $\int_{-\infty}^{\infty}f(x)dx=1$ for any $x,\lambda$. So, using the hint, $f(x)=2 \phi(x)(1-\Phi(-\lambda x))=2\phi(x)-2\phi(x)\Phi(-\lambda x)$. Then integrating both sides in the range $(-\infty,\infty)$, I get $$\int_{-\infty}^{\infty}2\phi(x)\Phi(\lambda x)dx=\int_{-\infty}^{\infty}\{2\phi(x)-2\phi(x)\Phi(-\lambda x)\}dx$$ which, $$\int_{-\infty}^{\infty}2\phi(x)\Phi(\lambda x)dx=\int_{-\infty}^{\infty}2\phi(x)dx-\int_{-\infty}^{\infty}2\phi(x)\Phi(-\lambda x)dx=2-\int_{-\infty}^{\infty}2\phi(x)\Phi(-\lambda x)dx$$

Here's where I get stuck. If my logic is correct up to here, the only way that my $f(x)$ is a density function is that $\int_{-\infty}^{\infty}2\phi(x)\Phi(-\lambda x)dx=\int_{-\infty}^{\infty}2\phi(x)\Phi(\lambda x)dx$. But clearly $\Phi(\lambda x) \neq \Phi(-\lambda x)$ (unless $\Phi(0)$) since, in the question's hint, we are told that $\Phi(\lambda x)=1-\Phi (- \lambda x)$.

Then that means $\int_{-\infty}^{\infty}f(x)dx \neq 1$ and that $f(x)$ isn't a density function. Which can't be.

I am very confused as I cannot see what and where I have done wrong and why it is wrong. How do I go about solving this problem? Thanks

$\endgroup$
1
  • $\begingroup$ $$\int_{-\infty}^{+\infty} f(x)\,dx = \int_0^{+\infty} f(x) + f(-x)\,dx$$ $\endgroup$ Oct 28 '15 at 19:22
2
$\begingroup$

It is true that $\Phi(\lambda x) \neq \Phi(-\lambda x)$, but this doesn't prevent $$ \int_{-\infty}^{\infty}2\phi(x)\Phi(-\lambda x)dx=\int_{-\infty}^{\infty}2\phi(x)\Phi(\lambda x)dx\tag1 $$ from being true. To show (1), apply the substitution $u=-x$ to the LHS, and the fact that $\phi(u)$ is symmetric around $u=0$. (i.e., $\phi(-u)=\phi(u)$ for all $u$.)

$\endgroup$
1
  • $\begingroup$ Wonderful, thanks!! $\endgroup$
    – Kydo
    Oct 28 '15 at 19:37

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.